(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
Accuracy and precision are key terms in technical terminology in various fields that include research, engineering, medicine, finance and more. These concepts play a key role in ensuring the reliability, validity and clarity of measurements, data and information. Understanding accuracy and precision is essential for professionals to communicate effectively in their field and make informed decisions based on reliable information. This comprehensive study delves into the nuanced meanings of the technical terminological accuracy and precision, their importance across disciplines, and how these concepts interact[1].